Penguatan Peran Ibu dan Kader Posyandu: Implementasi PHBS dan Inovasi Cemilan Bergizi dalam Pencegahan Stunting - Widia Dara; Dewi Yudiana Shinta; Ikhwan Resmala Sudji; Def Primal; Melly Siska Suryani; Muhammad Diki Juliandi (CANANG: Jurnal Pengabdian Masyarakat, 2026)
Stunting remains a public health issue in many rural and urban areas of Indonesia, linked to hygiene practices, child-rearing practices, and children’s nutritional intake. Posyandu volunteers and homemakers play a key role in prevention through behavioral change and the provision of nutritious complementary foods. This activity aims to strengthen the capacity of mothers and posyandu cadres in implementing Clean and Healthy Living Behaviors (PHBS) and developing recipes for local nutritious snacks to reduce the risk of stunting in toddlers. The expected benefits of this activity include improved knowledge and practice of PHBS, enhanced skills in preparing nutritious snacks, and increased availability of nutritious complementary foods in households, which has the potential to reduce the incidence of stunting in the medium term. Methods: The program was implemented through a one-day integrated education session that included PHBS education, demonstrations of preparing nutritious snacks using local ingredients, recipe demonstrations, hands-on practice sessions, and nutrition counseling. There were 30 participants (30 mothers and toddlers and 8 Posyandu cadres) in Padang Sarai Village, at the Kenanga 13 Posyandu. Evaluation used pre- and post-tests for knowledge and skills, observations of PHBS practices, as well as taste tests and nutritional analysis of simple snacks. Results: Following the intervention, there was an average increase of 42% in PHBS knowledge scores and 55% in skills for preparing nutritious snacks compared to pre-intervention levels. Observations showed that 70% of households implementing at least three essential healthy lifestyle practices (handwashing, food sanitation, and safe food storage). The snack recipes developed meet local nutritional standards (energy, protein, and essential micronutrient content) and received high taste acceptance ratings in panel testing. Conclusion: Strengthening the roles of mothers and posyandu volunteers through PHBS training and nutritious snack innovations has been shown to improve knowledge, skills, and household practices that support stunting prevention